If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 3(x + -3) = 2(3x + -4) Reorder the terms: 6 + 3(-3 + x) = 2(3x + -4) 6 + (-3 * 3 + x * 3) = 2(3x + -4) 6 + (-9 + 3x) = 2(3x + -4) Combine like terms: 6 + -9 = -3 -3 + 3x = 2(3x + -4) Reorder the terms: -3 + 3x = 2(-4 + 3x) -3 + 3x = (-4 * 2 + 3x * 2) -3 + 3x = (-8 + 6x) Solving -3 + 3x = -8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -3 + 3x + -6x = -8 + 6x + -6x Combine like terms: 3x + -6x = -3x -3 + -3x = -8 + 6x + -6x Combine like terms: 6x + -6x = 0 -3 + -3x = -8 + 0 -3 + -3x = -8 Add '3' to each side of the equation. -3 + 3 + -3x = -8 + 3 Combine like terms: -3 + 3 = 0 0 + -3x = -8 + 3 -3x = -8 + 3 Combine like terms: -8 + 3 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667
| 5x+7=6x+5 | | 2(2r-8)/5=2r-5/4 | | 14-w=5 | | e^7-4x=5 | | 7b^2+18b+8=0 | | 3x+4+8x+4+x=180 | | 6-r=5 | | 9x-3=9(x+3) | | 0=(-16x^2+64x+336) | | (x+4)8=64 | | 5+4d=85 | | 9x^2+x-1=9x^2+x+7 | | 14-z=6 | | 16+x=16 | | 5(x-3)-10=20 | | 8x-22=-50 | | 4(3y-1)=5y+11 | | a^2+18a+81= | | 18-k=9 | | s=6r+ph | | 1+2x=4(x+2)-3(x-3) | | -2(-2-2.66y)-5y=3 | | 4(3y-1)=5x-11 | | 9y^2+9y-10= | | 18-4x+8x=-2(-8x+9) | | 30x=4(3a+5)-7a | | -3x+7(7x-5)=195 | | =ab+8x+2b+16 | | 5(2x+5)=-11 | | 8y+16-8y=-3 | | Y^2=52 | | z-4=2 |